Bond men made free : medieval peasant movements and the English rising of 1381 - Hilton, R. H. (Rodney Howard), 1916-2002. (London ; New York : Routledge, 2003)
This account of the Peasant's Revolt of 1831 remains the classic authoratative text on the 'English Rising'.
Book Cover; Title; Contents; Acknowledgements; Abbreviations; A New Introduction; Old Introduction; The Nature of Medieval Peasant Economy; Early Movements and their Problems; Mass Movements of the Later Middle Ages; The Events of the Rising; The General Background; The Areas of Revolt; Social Composition; The Allies of the Rebels; Organization and Aims; Conclusion; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Tyler's Insurrection, 1381.; Great Britain -- History -- Richard II, 1377-1399.; Peasant uprisings -- England -- History -- To 1500.; Insurrection de Tyler, 1381.; Grande-Bretagne -- Histoire -- 1377-1399 (Richard II); HISTORY; Peasant uprisings; England; Great Britain; To 1500; History